2011
DOI: 10.1176/ps.62.5.pss6205_0484
|View full text |Cite
|
Sign up to set email alerts
|

Staff Perceptions and Organizational Factors as Predictors of Seclusion and Restraint on Psychiatric Wards

Abstract: These findings represent the first stage of a research program aimed at reducing use of seclusion and restraint in psychiatric settings. They underscore the importance of evaluating a variety of factors, including perceptions of safety and violence, when examining reasons for use of these controversial interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 54 publications
1
41
0
1
Order By: Relevance
“…De Benedictis et al [39] found that coercive measures were more frequently adopted when staff perceived great expressions of anger and aggression in other team members and when safety measures in the workplace were insufficient. As regards staff composition, Bowers et al [40] reported an inverse association between the number of junior medical doctors and the use of restraint, while the number of nurses was positively associated with a higher use of restraint.…”
Section: Predictors Of Use Of Coercive Measuresmentioning
confidence: 99%
“…De Benedictis et al [39] found that coercive measures were more frequently adopted when staff perceived great expressions of anger and aggression in other team members and when safety measures in the workplace were insufficient. As regards staff composition, Bowers et al [40] reported an inverse association between the number of junior medical doctors and the use of restraint, while the number of nurses was positively associated with a higher use of restraint.…”
Section: Predictors Of Use Of Coercive Measuresmentioning
confidence: 99%
“…De Benedictis et al . ; Nijman ), yet there is also still an abundance of evidence that shows that this position is still pervasive for some (Davison ; NICE ; Papadopoulos et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of intrusive measures has been criticized for various reasons. Inpatients have reported its negative impact, such as fear, anger, shame, and feelings of being abandoned (De Benedictis et al . 2011; Duxbury et al .…”
Section: Introductionmentioning
confidence: 99%
“…2005). There is a general growing concern among practitioners and health policy makers that these intrusive measures are countertherapeutic (Curie 2005; De Benedictis et al . 2011; Donovan et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation